Aggregatibacter actinomycetemcomitans infection in a 15-year-old boy with pulmonary empyema: a case report and review of literature - Maria Alessia Mesturino; Carol Bitetti; Anna Clemente; Andrzej Krzysztofiak; Laura Lancella; Roberta Lombardi; Laura Cursi; Elena Boccuzzi; Anna Maria Musolino; Alberto Villani (BMC, 2023)
Abstract Background Aggregatibacter actinomycetemcomitans (Aa), previously known as Actinobacillus actinomycetemcomitans, is a slow-growing Gram-negative coccobacillus, member of the HACEK group of bacteria colonizing oral flora. Besides causing infectious diseases in the oral cavity such as dental caries and periodontitis, it is responsible for severe extra-oral infections secondary to hematogenous spread or aspiration, such as endocarditis, soft tissue abscesses and osteomyelitis. The diagnosis depends on prolonged bacterial culture of biological material obtained through biopsy. Aa is susceptible to most antibiotics but complete eradication often requires a long term treatment. Case presentation We report the case of a 15-year-old previously healthy boy diagnosed with both pulmonary empyema and subphrenic chest wall abscess caused by Aa. He was admitted to our Pediatric Emergency department for evaluation of a right mass associated with marked asthenia and dry cough. After radiological findings etiological diagnosis was made by culture of fluid drainage of pleural empyema. He started empirical antibiotic therapy with intravenous piperacillin/tazobactam, whose sensibility was confirmed by the antibiogram, then, for occurrance of hepatopathy it was switched to ciprofloxacin: the patient almost completely recovered after 6-month therapy. Conclusions Extra-oral infections caused by Aa are extremely rare, especially in children, and not well described yet. To our knowledge, there is only another similar case described in literature. However, the case described in our manuscript represents the only one presenting with pulmonary empyema without involvement of lung parenchyma in children. We also conducted a brief review of published cases of Aa infection in the pediatric population. This case report reminds us the importance of an accurate inspection of the oral cavity during the examination of pediatric patients.